Remote Monitoring of Patients with Heart Failure: Characteristics of Effective Programs and Implementation Strategies - Teleanu IC; Bejan GC; Poiană IR; Mîrșu-Păun A; Dumitrescu SI; Stănescu AMA (Vascular Health and Risk Management, 2025)
Ioana Camelia Teleanu,1 Gabriel Cristian Bejan,1 Ioana Ruxandra Poiană,1 Anca Mîrșu-Păun,1 Silviu Ionel Dumitrescu,2,3 Ana Maria Alexandra Stănescu1,2,4,5 1“Carol Davila” University of Medicine and Pharmacy, Bucharest, Romania; 2“Carol Davila” Central Military Emergency University Hospital, Bucharest, Romania; 3Faculty of Medicine, “Titu Maiorescu” University, Bucharest, Romania; 4Academy of Romanian Scientists (AOSR), Bucharest, Romania; 5“Emil Palade” Center of Excellence for Young Researchers EP-CEYR The Academy of Romanian Scientists AOSR, Bucharest, RomaniaCorrespondence: Gabriel Cristian Bejan, Email cristian.bejan@umfcd.ro Anca Mîrșu-Păun, Email anca.mirsu-paun@rez.umfcd.roBackground and Objectives: Although the effectiveness of remote monitoring (RM) has been extensively studied, a focus on the post-pandemic time period is needed given the social changes and technology advances since this global event occurred.Aim: The present paper responds to this need by reviewing post-pandemic research, to determine if RM of patients with heart failure (HF) using non-implantable devices represents an effective strategy.Materials and Methods: A systematic literature review was conducted using PubMed and PMC, and the number of articles included was 19.Results: A total of 3,031 patients participated in the 19 studies in this review, who had HF (NYHA class I–IV). Most frequent outcomes of interest were: rates of hospitalization (13 studies), death (5 studies), adherence to medications / healthy behaviors (4 studies), associated costs (4 studies), symptom intensity or frequency (3 studies), etc. The studies included in this review unanimously presented significant findings in favor of RM.Conclusion: The post-pandemic research targeting RM of patients with HF presents more homogenous results to support this type of intervention, as compared to the heterogeneity of the pre-pandemic research.Keywords: heart failure, remote monitoring, medical technology, prevention